2012
DOI: 10.1155/2012/192192
|View full text |Cite
|
Sign up to set email alerts
|

Hymenoptera Venom Immunotherapy: Tolerance and Efficacy of an Ultrarush Protocol versus a Rush and a Slow Conventional Protocol

Abstract: Background and Objective. Various venom immunotherapy (VIT) protocols are available for Hymenoptera allergy. Although adverse reactions (ADRs) to VIT are widely reported, controlled trials are still needed. We conducted a randomized prospective study to evaluate ADRs and the efficacy of three VIT regimens. Methods. 76 patients with Hymenoptera allergy, aged 16–76 years, were randomized to receive an ultrarush protocol (group A: 27 patients), a rush protocol (group B: 25), or a slow protocol (group C: 24). Aque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 38 publications
1
17
0
1
Order By: Relevance
“…In a recent Cochrane Review, the percentage of nonprotection was 2.7% in treated patients compared with 39.8% in patients not undergoing immunotherapy [156]. Regarding vespid venom, protection is between 91% and 96%, while for bee venom it ranges between 77% and 84% [14,90,[157][158][159][160][161][162][163][164][165][166][167]. Studies performed on European populations, including Italian cases, show that about 70% of treated patients are allergic to vespids [164,166].…”
Section: Clinical Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent Cochrane Review, the percentage of nonprotection was 2.7% in treated patients compared with 39.8% in patients not undergoing immunotherapy [156]. Regarding vespid venom, protection is between 91% and 96%, while for bee venom it ranges between 77% and 84% [14,90,[157][158][159][160][161][162][163][164][165][166][167]. Studies performed on European populations, including Italian cases, show that about 70% of treated patients are allergic to vespids [164,166].…”
Section: Clinical Efficacymentioning
confidence: 99%
“…However, some authors do not consider rush or ultrarush induction protocols to be dangerous, since they were able to demonstrate a low risk of systemic reactions and a safety profile equivalent to or even better than slower protocols [163,[209][210][211].…”
Section: Adverse Reactionsmentioning
confidence: 99%
“…Few prospective studies have compared buildup protocols of venom immunotherapy [7][8][9][10], and no studies to date have compared a conventional 9-week protocol with clustered 3-and 4-week protocols. Buildup protocols are difficult to compare given the many differences between them (eg, patients selected, protocols used, extracts, and recording of adverse reactions), thus no doubt explaining why the prevalence of systemic reactions reported in the literature is so variable, ranging from 2% [11] to 21% [12].…”
Section: Discussionmentioning
confidence: 99%
“…Standard protocols (lasting 8-15 weeks), rush protocols (4-7 days), and ultrarush protocols (1-2 days) can all be used. Ultrarush protocols have been shown to be safe [9,12,[15][16][17]; however, other prospective studies have shown a rapid increase in dose to be an independent risk factor for adverse systemic reactions [13,18]. In the case of ultrarush protocols, this risk is increased 1.8-fold, although the protocols are costeffective [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…A lower, 50 mg dose of venom (not commercially available for jumper jack ant) in this experimental study [39] was associated with fewer SARs, but there were concerns about optimal efficacy using this dose. However, Patella et al [40] found that individuals randomized to an ultrarush protocol using either honeybee or yellow-jacket venoms did not have a significantly higher number of SARs during buildup or maintenance compared with those who received rush or standard buildup protocols. Ultrarush protocols also are effective in children but are associated with a significant risk of SARs.…”
Section: Selection Of Venoms and Treatment Protocolsmentioning
confidence: 99%